Mathematics anxiety and primary school teachers : the histories, impacts, and influences : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Education at Massey University, Manawatū, New Zealand - Whyte, Julie Margaret (Massey University, 2022)
Maths anxiety is understood to be a pervasive and global phenomenon. What is not so well understood is primary teachers’ experience of this anxiety. This study sought to provide a clearer understanding of teachers’ maths anxiety. Drawing on an interpretivist epistemology, framed by a sociocultural theoretical perspective, and using qualitative semi-structured interviews, the study provides a rich description of the personal histories and professional lives of 12 primary teacher participants who self-reported as experiencing maths anxiety. Each participant offered a unique, personal history of the development of maths anxiety. It was found to develop from a jumble of interactions from multiple sources and with multiple consequences. The teachers’ responses to anxiety around mathematics were wide ranging and included cognitive, affective, physiological, and neural reactions. In attempts to manage their anxiety, participants created specific strategies for particular situations. Amongst these management strategies were distraction and avoidance, eliciting support from trusted individuals, choosing to confine their teaching to lower year-level classes, and lengthy preparation to ensure they, themselves, understood the mathematics. Participants attempted to keep their anxiety hidden from others during their professional roles. Professional development was found to be a context in which the anxiety intensified. In professional development contexts, rather than focusing on new learnings and understandings, the participants focused on their anxiety. As a result, they failed to enhance their mathematical knowledge and failed to develop understanding of how mathematics might be taught. Their lack of confidence in their own knowledge impacted on their classroom teaching to the extent that, where possible, they scheduled less time for mathematics than other subject areas. Since such anxiety management strategies are not conducive to teacher growth and are likely to have negative consequences for students, this study has demonstrated that a carefully paced and sensitive approach needs to be taken by schools and providers of mathematics professional development courses.
Keywords: Math anxiety; Mathematics teachers; Career development; Mathematics; Study and teaching (Elementary); 390109 Mathematics and numeracy curriculum and pedagogy; 390307 Teacher education and professional development of educators